If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(-3x)(-2y + 1) + -1(-1y)(4 + -5x) = 0 Remove parenthesis around (-3x) -2 * -3x(-2y + 1) + -1(-1y)(4 + -5x) = 0 Reorder the terms: -2 * -3x(1 + -2y) + -1(-1y)(4 + -5x) = 0 Multiply -2 * -3 6x(1 + -2y) + -1(-1y)(4 + -5x) = 0 (1 * 6x + -2y * 6x) + -1(-1y)(4 + -5x) = 0 (6x + -12xy) + -1(-1y)(4 + -5x) = 0 Remove parenthesis around (-1y) 6x + -12xy + -1 * -1y(4 + -5x) = 0 Multiply -1 * -1 6x + -12xy + 1y(4 + -5x) = 0 6x + -12xy + (4 * 1y + -5x * 1y) = 0 Reorder the terms: 6x + -12xy + (-5xy + 4y) = 0 6x + -12xy + (-5xy + 4y) = 0 Combine like terms: -12xy + -5xy = -17xy 6x + -17xy + 4y = 0 Solving 6x + -17xy + 4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 6x + -17xy + 4y + -4y = 0 + -4y Combine like terms: 4y + -4y = 0 6x + -17xy + 0 = 0 + -4y 6x + -17xy = 0 + -4y Remove the zero: 6x + -17xy = -4y Combine like terms: -4y + 4y = 0 6x + -17xy + 4y = 0 The solution to this equation could not be determined.
| 4(14)+22=x | | 6.2a+15=64.6 | | 5-3x-4+3x=0 | | (5a-2)+3g(2a)ifg(x)=x^2-5x+8 | | */4=28 | | 9+2x-2=5x+13-2x | | C(x)=-.5x^2+60x | | 16x-7=20x-91 | | x(7+5)=2x^2-17x+48 | | X+2=5x+38 | | -x+.75y=-6 | | (-6)+(-15)= | | 2x-7=18x-39 | | -1=b/4-7= | | 3(1+2x)=-8 | | 7x+1=6x+12 | | 14=.2*70 | | (-3)+(-10)= | | 14n=6 | | 25x-20y=690 | | 3x+4x(x-2)=4x-5 | | 8t-10-3t=20 | | H=9piem | | 1+1+X=69 | | 242/b=44 | | 3n-2÷5=7/10= | | (-3)+(-15)= | | 15x+5+(22x+4)=120 | | 3(3)+2y=9 | | 13=x^2-0.20x | | 9x^2+18x+45=0 | | 2(2x+5)-5x=12 |